Developmental toxicity in embryo-larval zebrafish (Danio rerio) exposed to strobilurin fungicides (azoxystrobin and pyraclostrobin). (February 2020) - Kumar, N.; Willis, A.; Satbhai, K.; Ramalingam, L.; Schmitt, C.; Moustaid-Moussa, N.; Crago, J.
Abstract: Azoxystrobin and pyraclostrobin are broad spectrum strobilurin fungicides that have been measured in the aquatic environment. Strobilurins inhibit mitochondrial respiration by binding to the mitochondrial respiratory complex III. The goal of this study was to investigate mitochondrial dysfunction and oxidative stress in the developing zebrafish from exposure to azoxystrobin and pyraclostrobin. Exposure studies were performed where zebrafish embryos were exposed to azoxystrobin and pyraclostrobin at 0.1, 10, 100 μg/L from 4 hpf to 48 hpf to measure mitochondrial dysfunction and oxidative stress mRNA transcripts, and 5 dpf to measure movement, growth, oxygen consumption, enzymatic activities, and mRNA transcripts. Results from this study indicated that there was a significant reduction in both basal and maximal respiration at 48 hpf in zebrafish exposed to 100 μg/L of pyraclostrobin. There was no difference in oxidative stress or apoptotic mRNA transcripts at 48 hpf, indicating that the two strobilurins were acting first on mitochondrial function and not directly through oxidative stress. At 5 dpf, standard body length was significantly reduced with exposure to pyraclostrobin and azoxystrobin exposure as compared to the control. These reductions in apical endpoints corresponded with increases in oxidative stress and apoptotic mRNA transcripts in treatment groups at 5 dpf indicating that strobilurins' exposure followed the adverse outcome pathway for mito-toxicants. Our results indicate that strobilurins can decrease mitochondrial function, which in turn lead to diminished growth and movement. Highlights: Pyraclostrobin exposure significantly reduced body length and oxygen consumption in larval zebrafish. Pyraclostrobin decreased mitochondrial bioenergetics at 100 μg/L in 48 hpf zebrafish embryo. Azoxystrobin and pyraclostrobin induced oxidative stress transcripts at an environmentally relevant concentration in 5 dpf zebrafish.